Neurogenic Shock Simulation Case - Cullen Hegarty; Emily Binstadt (Association of American Medical Colleges, 2011)
Abstract This module contains a simulation case designed for use with a high-fidelity manikin (Laerdal SimMan) that is mainly geared for residents. The goal is for the learners to appropriately manage the major trauma victim with spinal cord injury and neurogenic shock. The case is typically run with three to four emergency medicine residents who assume the role of airway doctor, exam performer, and team leader. Residents range from PGYI to PGYIII years. After the completion of the simulation, the participants are debriefed using the included guide. This case has now been run multiple times without any new issues or programming troubles. Evaluation data from participants revealed positive satisfaction with the case and realism, positive satisfaction with the debriefing and PowerPoint presentation, and subjective notes about confirmation of their knowledge of spine injury/neurogenic shock management and new knowledge obtained. No pre-and posttest are available for this case. Residents do comment verbally and on their evaluation forms that their confidence to manage a case similar to this is enhanced through this session.